Modifications of plasma 5-HT concentrations during the allergic bronchoconstriction in guinea pigs. (1st September 2013) - Arreola-Ramírez, José Luis; Vargas, Dr. Mario H.; Manjarrez-Gutiérrez, Gabriel; Alquicira, Jesús; Gutiérrez, Julio; Córdoba, Guadalupe; Campos-Bedolla, Patricia; Segura-Medina, Patricia
ABSTRACT: Several contractile mediators involved in the antigen-induced airway obstruction have been identified, but the role of 5-HT (5-hydroxytryptamine or serotonin) has been scantily investigated. In this work, the potential role of 5-HT in the allergic bronchoconstriction was evaluated through a pharmacological approach and plasma 5-HT measurement in blood samples from the right and left ventricles of anesthetized guinea-pigs. Intravenous 5-HT caused a dose-dependent increase of the lung resistance in anesthetized, nonsensitized guinea pigs. Likewise, in sensitized animals the antigenic challenge with ovalbumin also caused a transient bronchoconstriction (356 ± 60% the basal value), which was largely inhibited by the blockade of serotonergic receptors with methiothepin plus tropisetron (134 ± 10%, P = .007). Sensitized animals tended to have plasma 5-HT concentrations higher than nonsensitized controls, and shortly after the peak of the allergic bronchoconstriction the 5-HT levels in the left ventricle (blood flowing out from lungs) tended to be higher than in the right ventricle (blood entering the lungs), although data dispersion precluded the obtaining of statistical significance. Interestingly, the degree of bronchoconstriction highly correlated with the concentrations of 5-HT found in the left ventricle and measured either in platelet-rich plasma ( r = 0.97 P = .007) or platelet-poor plasma ( r = 0.97, P = .006). After the obstructive response subsided these correlations were lost, but now the degree of bronchoconstriction turned to be correlated with 5-HT concentration in platelet concentrate ( r = 0.76, P = .03). In conclusion, our results suggested that 5-HT is actively released from lungs during the antigenic challenge and that this autacoid is involved in the generation of the airway obstruction.